2020
DOI: 10.3847/1538-4365/abbee3
|View full text |Cite
|
Sign up to set email alerts
|

The K2 Galactic Archaeology Program Data Release 2: Asteroseismic Results from Campaigns 4, 6, and 7

Abstract: Studies of Galactic structure and evolution have benefitted enormously from Gaia kinematic information, though additional, intrinsic stellar parameters like age are required to best constrain Galactic models. Asteroseismology is the most precise method of providing such information for field star populations en masse, but existing samples for the most part have been limited to a few narrow fields of view by the CoRoT and Kepler missions. In an effort to provide well-characterized stellar parameters across a wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 72 publications
3
37
0
Order By: Relevance
“…Additionally, the available asteroseismic information is growing steadily as the analysis of data from the K2 campaigns progresses. The overlap between GALAH targets and K2 targets from campaign C1-C8 and C10-C18 has increased to more than 10 000 stars with measured asteroseismic max values (Zinn et al 2020) and spectroscopic information, and covers almost the entire red giant branch (log ∼1.5 − 3.0 dex) and helium-core burning red clump.…”
Section: Target Selectionmentioning
confidence: 99%
“…Additionally, the available asteroseismic information is growing steadily as the analysis of data from the K2 campaigns progresses. The overlap between GALAH targets and K2 targets from campaign C1-C8 and C10-C18 has increased to more than 10 000 stars with measured asteroseismic max values (Zinn et al 2020) and spectroscopic information, and covers almost the entire red giant branch (log ∼1.5 − 3.0 dex) and helium-core burning red clump.…”
Section: Target Selectionmentioning
confidence: 99%
“…The comparison of the results obtained by the three seismic pipelines (A2Z, COR, and pySYD) allowed us to build a list of confirmed detections constituted of 99 stars where at least two pipelines agree within 10% in ν max , as it has already been demonstrated that such scatter between pipelines is reasonable, particularly for low S/N cases (e.g., Zinn et al 2020). In the remainder of the paper, we refer to those 99 stars as "our sample.…”
Section: Finalizing the Sample Of Confirmed Detectionsmentioning
confidence: 99%
“…known planet hosts (APOGEE2_TARGET2 bit 11), 2. stars with a confirmed oscillation or granulation signal (APOGEE2_TARGET1 bit 30), 3. red giants that were targeted by the K2 Galactic Archaeology Program (GAP; Stello et al 2017) and not observed with HERMES, 4. GAP targets observed by HERMES (see Wittenmyer et al 2018;Sharma et al 2019;Zinn et al 2020), 5. M dwarfs in the unbiased sample from the Ancillary Science Program described in Appendix B.9 (APO-GEE2_TARGET3 bit 28).…”
Section: Apogee-k2 Surveymentioning
confidence: 99%